Steam Activation of Oil Shale to Enhance the Porosity of Produced Semicoke. Issue 4 (21st December 2022) - Pikkor, Heliis; Lees, Heidi; Konist, Alar; Järvik, Oliver; Maaten, Birgit
ABSTRACT: Finding a recycling method for waste materials is attracting increasing attention. In Estonia, semicoke from the shale oil industry is a material that can be used for adsorbent production. For this application, it is important to characterize the surface properties and enhance the porosity. In this study, different pyrolysis temperatures (from 500 to 800 °C) and steam activation parameters were applied to determine their influences on the surface properties of oil shale semicoke. It was found that pyrolysis at 700°C resulted in the highest Brunauer – Emmett–Teller surface area of 59 m 2 /g. To investigate the effect of activation, up to 70% vol of steam was added to the pyrolysis environment for different durations (15–60 min). Although the effect was relatively small, shorter activation times and less steam resulted in larger surface areas. The highest surface areas (68–69 m 2 /g) were achieved when activation was carried out for 15 to 30 min with 25–50% vol of steam in the environment after pyrolysis at 700°C. It can be concluded that longer activation and more steam causes widening and collapsing of some pore structures, resulting in a decrease in the surface area and total pore volume.